Embodied Auditory Display Affordances - Furlong, Dermot; Roddy, Stephen (My University, 2015)
The current paper takes a critical look at the current state of Auditory Display. It isolates naive realism and cogni- tivist thinking as limiting factors to the development of the field. An extension of Gibson’s theory of affordances into the territory of Embodied Cognition is suggested. The proposed extension relies heavily on Conceptual Metaphor Theory and Embodied Schemata. This is hoped to provide a framework in which to address the problem- atic areas of theory, meaning and lack of cognitive re- search in Auditory Display. Finally the current research’s development of a set of embodied auditory models in- tended to offer greater lucidity and reasonability in Audi- tory Display systems through the exploitation of embod- ied affordances, is discussed.
Proceedings of 12th Sound and Music Computing Conference
12th Sound and Music Computing Conference
Keywords: Auditory Display; Embodied Cognition; Conceptual Metaphor Theory; Embodied Schemata; Creative Technologies; Telecommunications; Auditory Display; Human-Computer Interaction; Sonification